Edukasi Tentang Pernikahan Dini Dan Kesehatan Reproduksi Serta Pengenalan Nilai-Nilai AIK Sebagai Upaya Pencegahan Stunting Mulai Usia Dini - Asmeri Lamona; Meta Rikandi; Desi Asmaret; Chintia Pratama Putri; Rahmad Saputra (Universitas Alifah Padang, 2024)
The condition of stunting in children is cause by interrelated multidimensional factors. This stunting condition is influenced by several factors including maternal factors, infant and toddler factors, as well as social, economic, and environmental factors. Currently, adolescents are one of the government’s targets in reducing the incidence of stunting, because adolescents are a group that has a large role in determining the future. One of the causes of stunting is early marriage. Based on data from the ministry of religion of Padang City in 2023, there were 26 marriages under the age of 19 in 2022. The target in this community service is students of SMA Muhammadiyah I Padang City with the aim of increasing adolescent knowledge from an early age. The method of implementing the activity is carried out by providing education about early marriage, reproductive health, introduction to the values of AL Islam Kemuhammadiyahan and product introduction as an effort to prevent stunting in adolescents. The results of this service were 73% knew about stunting, 53% knew about reproductive health, 86% knew about early marriage and 55% had consumed vegetable milk. However, most students before being given education do not understand the relationship between stunting and adolescents. It is expected that schools will provide education to adolescents through student activity organizations to avoid stunting in the next generation.